Rola bankowości centralnej w zapewnieniu stabilności systemu finansowego. Nowe wyzwania w obliczu kryzysu - Grodecka, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This paper covers the impact of the global financial crisis on the perception of central banks’ role in preserving the stability of financial system. Current crisis has shaken the foundations of deceptively comfortable pre-crisis central banking setting as well as revealed its weaknesses, i.e.: passive attitude of central banks towards the build-up of financial imbalances, ineffectiveness of monetary policy transmission mechanism, lack of macroeconomic perspective with reference to regulations and supervision, threats to operational independence of central banks due to the risk of fiscal dominance. Hence, it highlighted the challenges rising ahead, which central banks need to remonetary policy transmission mechanism, lack of macroeconomic perspective with reference to spond to conducting a post-crisis operational and institutional reform, i.e.: adopting a more symmetric and active approach throughout the economic cycle, including macroprudential frameworks and tools in regulations and supervision, establishing flexible inflation targeting, stronger safeguarding of central banks’ independence and better comprehending a global dimension of their policies. The sum of those core proposals, referred to as the new consensus, is induced by a substantial shift to financial system stability as the priority goal of central banks and the precondition of price stability and sustainable growth.
Keywords: bank centralny; stabilność; system finansowy; polityka pieniężna; polityka makroostrożnościowa